Outcome of patients with different stages of acute-on-chronic liver failure treated with artificial liver support system - Ma, Yuanji; Xu, Yan; Du, Lingyao; Bai, Lang; Tang, Hong (Frontiers in Medicine, 2024)
Background Elevated international normalized ratio of prothrombin time (PT-INR) is one of the key characteristics of acute-on-chronic liver failure (ACLF). Whether the staging of PT-INR has the ability to screen out subgroups of ACLF patients who would be more eligible for artificial liver support system (ALSS) treatment has not been studied in detail. Methods A previous study enrolled patients receiving ALSS treatment with regional citrate anticoagulation from January 2018 to December 2019. Patients with different PT-INR intervals were retrospectively enrolled: 1.3 ≤ PT-INR < 1.5 (Pre-stage), 1.5 ≤ PT-INR < 2.0 (Early-stage), 2.0 ≤ PT-INR < 2.5 (Mid-stage), and PT-INR ≥ 2.5 (End-stage). The Cox proportional hazards models were used to estimate the association between stages of ACLF or sessions of ALSS treatment and 90 day mortality. Results A total of 301 ACLF patients were enrolled. The 90 day mortality risk of Early-stage ACLF patients (adjusted hazard ratio (aHR) (95% confidence interval (CI)), 3.20 (1.15–8.89), p = 0.026), Mid-stage ACLF patients (3.68 (1.34–10.12), p = 0.011), and End-stage ACLF patients (12.74 (4.52–35.91), p < 0.001) were higher than that of Pre-stage ACLF patients, respectively. The 90 day mortality risk of Mid-stage ACLF patients was similar to that of Early-stage ACLF patients (1.15 (0.69–1.94), p = 0.591). The sessions of ALSS treatment was an independent protective factor (aHR (95% CI), 0.81 (0.73–0.90), p < 0.001). The 90 day mortality risk in ACLF patients received 3–5 sessions of ALSS treatment was lower than that of patients received 1–2 sessions (aHR (95% CI), 0.34 (0.20–0.60), p < 0.001), whereas the risk in patients received ≥6 sessions of ALSS treatment was similar to that of patients received 3–5 sessions (0.69 (0.43–1.11), p = 0.128). Conclusion ACLF patients in Pre-, Early-, and Mid-stages might be more eligible for ALSS treatment. Application of 3–5 sessions of ALSS treatment might be reasonable.